2011
DOI: 10.1167/iovs.10-7049
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 13 Immunostaining in Corneal Impression Cytology for the Diagnosis of Limbal Stem Cell Deficiency

Abstract: K13 has shown to be a new marker of conjunctival differentiation. The immunocytochemical search for the K13/K19 couple by corneal IC provides a simple and reliable method for diagnosing LSCD, whereas the level of K12 could provide a score of disease severity. On the other hand, the authors question the corneal specificity of K3 as conventionally established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 24 publications
2
30
0
3
Order By: Relevance
“…Previous studies revealed that K19-positive cells were present on the corneal surface in a higher proportion (82%) than goblet cells (59%) in patients with clinical definite LSCD, 28 and that K13 might be more specific than K19 in the diagnosis of LSCD. 27 Our results supported these studies with the observation of K19-and K13-positive epithelial invasion into the corneal surface after BAC treatment in BALB/c mice on day 28, in the absence of MUC5AC-positive goblet cells. Based on these issues, we considered that although the presence of goblet cells is needed to confirm the diagnosis of LSCD, their absence does not exclude the diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies revealed that K19-positive cells were present on the corneal surface in a higher proportion (82%) than goblet cells (59%) in patients with clinical definite LSCD, 28 and that K13 might be more specific than K19 in the diagnosis of LSCD. 27 Our results supported these studies with the observation of K19-and K13-positive epithelial invasion into the corneal surface after BAC treatment in BALB/c mice on day 28, in the absence of MUC5AC-positive goblet cells. Based on these issues, we considered that although the presence of goblet cells is needed to confirm the diagnosis of LSCD, their absence does not exclude the diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…Immunolabeling of histological sections was therefore performed to detect clues on day 28. Cumulative evidence indicated that the identification of conjunctiva-specific K19-or K13-positive epithelial cells on the corneal surface would be a simple and practical method to identify LSCD, 9,27 as the invasion of conjunctiva remained constant under various ocular surface stresses. Previous studies revealed that K19-positive cells were present on the corneal surface in a higher proportion (82%) than goblet cells (59%) in patients with clinical definite LSCD, 28 and that K13 might be more specific than K19 in the diagnosis of LSCD.…”
Section: Discussionmentioning
confidence: 99%
“…13 Mild LSCD was defined by the absence of visual axis involvement despite peripheral neovascularization and conjunctivalization, whereas severe LSCD was considered in case of complete conjunctivalization and neovascularization, corneal scarring or thinning. Between both, LSCD was scored as moderate.…”
Section: Human Samplesmentioning
confidence: 99%
“…14-17 K13, K19, and K7 have recently been reported as markers of the conjunctival-type differentiation. 12,[18][19][20] However, the conjunctival specificity of K19 has recently been questioned, 4,13,21,22 as has the corneal specificity of K3, 4,11,13,20,23,24 strongly suggesting that the actual expression patterns of keratin in the ocular surface epithelium are not as clear-cut as the current dogma suggests.…”
mentioning
confidence: 99%
“…Cytokeratin 13 and 19 are both markers of conjunctival epithelium and as such were used in this study to signify the extent of conjunctivalization. [17][18][19][20][21] iovs.arvojournals.org j ISSN: Contact lenses (CLs) are hugely popular, mainstream medical devices used to improve vision. They are also routinely used as bandages to aid corneal healing due to disease or surgery.…”
mentioning
confidence: 99%